Hermeneutics of Revelation Truth: Attempts to Find Meaning Across the Ages in the Qur'an - Abid Nurhuda; Muhammad Hariyadi; Muhammad Al Fajri (Fanshur Institute, 2026)
This research begins with the realization that the Qur'an, as divine revelation, possesses both finality and openness. Its finality guarantees the authority and authenticity of God's message, while its openness allows the text to continue speaking to humanity across time and space. Using a hermeneutic approach, this research seeks to uncover the dialectic between the two in order to discover the meaning of revelation that is relevant to the various challenges of our time. Hermeneutics is positioned not only as an interpretive method but also as an epistemological framework that places the reader in a critical dialogue with the text, its historical context, and contemporary reality. The results show that applying the hermeneutics of revealed truth can prevent two extremes: the rigid consolidation of meaning within a single historical horizon, and the detachment of the text from its divine roots through overly liberal interpretations. By emphasizing the universality of Qur'anic values such as justice, mercy, and moral responsibility, hermeneutics presents an Islam that remains relevant. This relevance is evident in its ability to contribute to modern issues such as social justice, gender equality, the environmental crisis, and intercivilizational dialogue. Thus, this research confirms that the hermeneutics of revealed truth is a constructive effort to maintain the sacredness of the text while simultaneously revitalizing its transformative power. The Quran exists not only as a spiritual heritage but also as a source of inspiration for the development of a just, inclusive, and global humanity-oriented civilization.